A gênese da concepção de amor: um estudo sob a ótica da moralidade - Alves, Ariadne Dettmann (2011)
Reflecting on the importance of virtues in moral development, our goal was to investigate the children love concepts. We interviewed 40 students, 6 and 9 years old, in a private school in Vila Velha-ES, according to the clinical method proposed by Piaget. We analyzed the cited examples of love, what would be the most and least important, the judgment about the possibility of loving a child of the opposite sex, of same sex, a friend, an enemy and a stranger. We found that children have an ample concept; including mainly giving love to others" and love for (a) particular person/people, which increased with age, and actions with love", which showed a decrease. These examples were also considered most important by participants, and love for (a) particular person/people increased with age. On the least important examples of love, mostly students aged 9 said they did not exist, and the 6-years old elected the actions with love". Most respondents stated the possibility of loving a child of the opposite sex and same-sex friend. However, a minority has confirmed the relationship of love for an enemy, and still less with a stranger. In general, the justifications referred to the existing ties, the positive consequence for oneself, positive feature of the love object and observation of lived experience, and tended to increase with age. We emphasize the importance of love in development and hope to encourage further discussion on this virtue, contributing to proposals for education in moral values.